2017
DOI: 10.1002/joc.5097
|View full text |Cite
|
Sign up to set email alerts
|

Connections between north‐central United States summer hydroclimatology and Arctic sea ice variability

Abstract: Arctic sea ice has been shrinking at unprecedented rates over the past three decades. These cryospheric changes have coincided with greater incidence of global extreme weather conditions, including increased severity and frequency of summer heatwaves and extreme rainfall events. Recent studies identify potential physical mechanisms related to Rossby wave and resonance theories that may attribute the observed changes in extreme summer weather patterns to Arctic sea ice decline. This study explores the linkages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
(159 reference statements)
0
11
0
Order By: Relevance
“…Our understanding of the processes is constantly evolving (e.g., [13,14]) with recent research suggesting that, among others, ASIE is potentially a controlling factor or interacts with (1) the Atlantic multidecadal oscillation (AMO; [14]); (2) the NAO [13,15]; (3) the western Pacific pattern (WP) and El Nino Southern Oscillation (ENSO; [15]); (4) declining summertime total kinetic energy and zonal flow [16]; (5) the Pacific Decadal Oscillation (PDO; [17]); (6) surface temperature extremes [10]; and (7) surface precipitation extremes [18,19]. An example of the evolution of our understanding of the linkages includes studies [13,20], which found that contrary to earlier work based on empirical data [2,5], model simulations show that lower levels of ASIE are associated with reductions in wintertime cold events in Northern Europe, not increases in these events.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the processes is constantly evolving (e.g., [13,14]) with recent research suggesting that, among others, ASIE is potentially a controlling factor or interacts with (1) the Atlantic multidecadal oscillation (AMO; [14]); (2) the NAO [13,15]; (3) the western Pacific pattern (WP) and El Nino Southern Oscillation (ENSO; [15]); (4) declining summertime total kinetic energy and zonal flow [16]; (5) the Pacific Decadal Oscillation (PDO; [17]); (6) surface temperature extremes [10]; and (7) surface precipitation extremes [18,19]. An example of the evolution of our understanding of the linkages includes studies [13,20], which found that contrary to earlier work based on empirical data [2,5], model simulations show that lower levels of ASIE are associated with reductions in wintertime cold events in Northern Europe, not increases in these events.…”
Section: Introductionmentioning
confidence: 99%
“…However, more generally our results indicate that high GBI winter anomalies are co-located with sea-ice anomalies, while there seems to be minimal influence of sea-ice anomalies on the recent significant increase in summer GBI. Greenland high-pressure blocking is a key measure of changes in North Atlantic and Northern Hemisphere atmospheric circulation and potential Arctic-mid-latitude climate linkages (e.g., Woollings et al, 2008;Davini et al, 2012a;Hall et al, 2015;Hanna et al, 2015;2016;Mattingly et al, 2015;2016;McLeod and Mote, 2016;Budikova et al, 2017;Ballinger et al, 2018). Blocking is generally used to describe a large, quasistationary mid-latitude anticyclone that persists for at least a few days and is associated with increased large-scale meridional flow (Rex, 1950), but there is no clear consensus on an exact definition (e.g., Woollings et al, 2008).…”
mentioning
confidence: 99%
“…These modifications suggest the presence of ridge‐trough‐ridge pattern of atmospheric circulation and a stationary wave train. Such features have been documented as responses to declining sea ice in various areas of the Arctic including HB and Labrador Sea (Budikova et al, ; Vihma, ). The resultant atmospheric flow would bring consistent streams of warm air from the desert southwest into the study area and increase the potential for heat waves to form throughout the summer season.…”
Section: Resultsmentioning
confidence: 98%
“…Rossby wave and resonance theories have been used to argue that Arctic sea ice decline and Arctic warming can lead to NH atmospheric flow modifications with a potential for increased persistence and blocking events in the middle latitudes via a weakening of the poleward thermal gradient, mean zonal winds and thermal winds, reduction in total atmospheric kinetic energy, and an increase in the amplification of quasistationary wave numbers 6–8 (Coumou et al, , ; Francis & Vavrus, , ; Tang et al, ). These alterations provide more conducive environments for the development of summertime extreme weather events across the NH midlatitudes (Budikova & Chechi, ; Budikova et al, ; Coumou et al, ; Screen et al, ). In recent decades, low summer sea ice has been associated with the negative phase of the North Atlantic Oscillation (NAO) with increased (decreased) upper‐level geopotential heights (zonal wind speeds) across the polar cap and a northward shift in the subpolar jet stream, leading to increased ridging and southerly advection of warm air from the subtropics (Budikova & Chechi, ; Francis & Vavrus, ; Mann et al, ; Schubert et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation